The Crucial Role of CS in Systems and Synthetic Biology. - Cohen, Jacques (Communications of the ACM, 2008)
The article discusses the linking of computer science with biology. The author says that over the next few decades the hardware-software paradigm will be challenged by synthetic biology, which will utilize living organisms to perform tasks. Synthetic biology will allow scientists to perform tasks like cleaning the environment, making new drugs, and detecting dangerous chemicals. The author details the current state of computer science and the ways that synthetic biology is expected to change the field.